A typical trace pattern in some violent and selfish-violent crimes committed by minors - Pilyukov, Yurii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
One of the most important elements of the forensic characterization of crimes is the trace pattern, which is displayed in the form of typical traces characteristic of minors. It has been proven that the most typical crimes committed by minors are criminal offenses of a violent and selfish-violent nature, which include: murder, intentional infliction of bodily harm, theft, robbery, robbery, extortion, crimes against sexual freedom and sexual integrity of a person, hooliganism etc. The purpose of the article is to highlight the features of the trace picture that is formed during the commission of certain violent and self-serving violent crimes by minors and its significance for the investigation of criminal offenses of the specified category. The commission of criminal offenses of the specified category by minors is accompanied by the formation of a number of typical traces, the characteristic features of which depend on the methods of their commission, objects of encroachment, place, time and psychophysiological features of the minor criminal. The specificity of the psychophysiological characteristics of teenagers, their social and mental immaturity, combined with the lack of criminal "experience" and professional skills, leads to leaving numerous traces of various origins at the scene of the incident. The trace pattern at the scene of the crime can also be influenced by the state of alcohol or drug intoxication, which is often in which minors are at the time of committing crimes. A change in the physical environment, the presence of tools used by criminals to commit a crime, personal belongings lost at the scene, traces of reflections - hands, feet, shoes, tools, micro-objects, and the victim’s body are considered to be a typical trace picture of the commission of robberies and robberies. , bruises, sores, open wounds, etc. Traces of violent actions, struggle and resistance of the victim, presence of separate elements of torn clothing, traces of blood, semen, skin epithelium, hair, saliva, presence of hematomas, wounds, bruises, etc. on the victim’s body are characteristic of rape. Characteristic signs of traces that indicate the commission of a crime by minors are forensically significant biological signs of their appearance that remained in the memory of witnesses and victims, as well as signs of human traces (hands, feet, shoes) found at the scene of the incident, the results of which research , can confirm or deny the proposed version about the commission of a crime by a minor. Thus, the involvement of a minor in a crime can be evidenced by the presence at the scene of a headdress, handprints, shoes, the size characteristics of which will correspond to the criminal’s teenage age. Conclusions. The following pattern in individual violent and selfish-violent crimes committed by minors depends on the objects of the offense, the methods, time and place of their commission, as well as the psychophysiological characteristics of the person of the minor offender. The value of the trace picture in the investigation of crimes committed by minors is determined from the point of view of its informativeness of the totality of information carried by the traces left behind. Trace analysis can provide the necessary information to identify other evidence, establish a model of a criminal event, put forward versions, plan and choose the direction of the investigation, as well as predict the possible behavior of a juvenile offender during investigative (search) actions.